Co-design of the Australian Prompt Response Network for a public-health focused intersectoral approach to information sharing on emerging drugs of concern - Krista J. Siefried; Krista J. Siefried; Krista J. Siefried; Krista J. Siefried; Penny Hill; Penny Hill; Brendan Clifford; Brendan Clifford; Brendan Clifford; Brendan Clifford; Jared Brown; Jared Brown; et al. (Frontiers in Public Health, 2025)
The rapid emergence of new psychoactive substances (NPS) and other emerging drugs of concern presents a significant global public health challenge, necessitating agile and interconnected drug information systems to identify and communicate risks. In Australia, responses have traditionally been localized, lacking a nationally coordinated system to rapidly share information about emerging drug threats. The National Center for Clinical Research on Emerging Drugs (NCCRED) collaborated with jurisdictional networks, clinicians, scientists, policy-makers, and peer organizations to co-design and co-produce the national Prompt Response Network (“PRN”). This process identified key components necessary to create an effective health-focused national network that supports and enhances existing and emerging jurisdictional and specialist early warning networks. The co-creation process resulted in several outputs, including a formalized national PRN group, an online knowledge exchange platform, a national website for disseminating drug alerts, and identified needs for a national drug signal database and an anecdotal reporting system. The PRN is the first Australian national public-health-focused mechanism for information exchange on new and emerging drugs and drug trends of concern. It provides the means for timely and responsive sharing of localized data, better informing risk assessment and facilitating a coordinated approach to public health responses and local and national preparation for emerging risks. Achieving this required mobilizing diverse disciplinary and community stakeholders toward a unified and collaborative response to preventing drug related harms.